STUDI GANGGUAN HUBUNG SINGKAT PADA TRANSFORMATOR DISTRIBUSI 20 KVA DI PT.PLN(PERSERO) AREA KOTA PONTIANAK - ., Riki Mambela (Fakultas Teknik, 2018)
In this study aims to conduct the study of 3 phase short circuit interference on 20 kVA distribution transformer, distribution transformer used as material of this research include: 160 kVA and 200 kVA transformer. Where this research activity is implemented in PT.PLN (Persero) Area Pontianak City. The results of the study show that: three phase short circuit that occurs at Distribution Depot KT 0234 located at Jalan Letjen Sutoyo (Pertamina Office) is 0,0371 pu or 5,354,9237 Ampere, three phase short circuit that occurs at Substation Distribution KT 0383 located at Jalan Sei. Raya Dalam (Raya Sei Lestari Complex) of0.0467 pu or 6,740,5644 Ampere and three phase short circuit that occurred at Distribution Depot KT 0907 located at Jalan M. Yamin (Office of Komplek Ari Karya Indah) of 0.0444 pu or 6,408,5880 Ampere.Of the three distribution substations, the maximum three phase short circuit current occurs at DistributorshipKT 0383 of 6,740,5644 Ampere, this is due to the small impedance or short repeater connecting the GI. Sei. Raya to Distribution Substation KT 0383. Keywords: disturbance in distribution transformer, three phase noise.